Suppression of excited states relative to the ground state in Pb-Pb collisions at s NN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (American Physical Society, 2018)
The relative yields of ϒ mesons produced in pp and Pb-Pb collisions at ffiffiffiffiffiffiffi sNN p ¼ 5.02 TeV and reconstructed via the dimuon decay channel are measured using data collected by the CMS experiment. Double ratios are formed by comparing the yields of the excited states, ϒð2SÞ and ϒð3SÞ, to the ground state, ϒð1SÞ, in both Pb-Pb and pp collisions at the same center-of-mass energy. The double ratios, ½ϒðnSÞ/ϒð1SÞPb−Pb/½ϒðnSÞ/ϒð1SÞpp, are measured to be 0.308 0.055ðstatÞ 0.019ðsystÞ for the ϒð2SÞ and less than 0.26 at 95% confidence level for the ϒð3SÞ. No significant ϒð3SÞ signal is found in the Pb-Pb data. The double ratios are studied as a function of collision centrality, as well as ϒ transverse momentum and rapidity. No significant dependencies are observed.